Service-Learning in Higher Education - Butin, D. author. aut Link
XXVI, 230 p.
Keywords: Advocates have positioned service-learning as a real-world, real-time opportunity for students to encounter academic knowledge in a meaningful and relevant manner. Service-learning in higher education settings offers a powerful alternative to traditional models of teaching and learning. Students are encouraged to develop links to local institutions, volunteer their time, and create a special bond between the university and the community in which they live. Service-learning has become a very popular alternative to standard courses in higher education and is gaining significant popularity. This book takes a serious look at the unintended consequences and alternative conceptualizations of this mode of learning and explores what it could offer us in the future.